On the Sustainability of Guideline Implementation - Juliane Köberlein, PhD; Julia Vent, MD, PhD; Ralph Mösges, FAAAAI, MD, PhD (World Allergy Organization Journal, 2010)
Background Allergic rhinitis (AR) is a disorder associated with a high financial burden and is considered an important risk factor for the development of asthma. The ARIA guideline (Allergic Rhinitis and its Impact on Asthma) addresses this problem and provides recommendations for treating allergic rhinitis. The objective of the present analysis was to estimate the compliance with guidelines among ear, nose and throat (ENT) specialists and general practitioners.Methods The data of 121,593 patients collected during 9 prospective observational studies carried out from 1998 to 2005 were examined using individual patient data meta-analysis method.Results Only 14.8% of patients with allergic rhinitis were treated according to the recommendations. Of the others, 73.8% received insufficient treatment. In addition, 36.1% of the patients who were treated by ENT specialists received therapy according to guidelines, whereas only 16% of the general practitioners heeded the recommendations. Patients suffering from rhinitis and asthma were treated by ENT specialists according to the ARIA guideline in 50% of cases. It could be observed that the rate of guideline compliance was highest in the year of publication.Conclusion The results are evidence of the successful implementation process of the ARIA guidelines. However, they have not yet found their way into the daily routine of general practitioners. Keywords: allergic rhinitis, treatment, guidelines, compliance, ARIA, ENT specialists